2018
DOI: 10.5539/jas.v10n9p142
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Growth of Genovese Basil in Response to Different Concentrations of Salts and Interaction of Sucrose and Activated Carbon

Abstract: Genovese basil has great economic potential; however, there is no established micropropagation protocol for this species. Therefore, this study aimed at assessing the in vitro growth of Genovese basil in response to different concentrations of salts in the Murashige and Skoog medium (MS) and interaction of sucrose and activated carbon. Two assays were conducted independently in an in vitro environment using the MS medium, regulators, agar, and five salt concentrations (0, 25, 50, 70 and 100%). In the second as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In this case, the actived charcoal did not restrict Cu and Zn uptake, as M3 and M5 media had higher amounts of these micronutrients (Table 4). These results corroborate those reported by Trettel et al (2018b), where Ocimum basilicum plantlets maintained in MS medium with 60 g L -1 of sucrose and 4.5 g L -1 of actived charcoal did not show an increased plantlets growth, and these micronutrients did not contribute to adsorption of Cu and Zn.…”
Section: Different Compositions Of Ms Mediumsupporting
confidence: 92%
“…In this case, the actived charcoal did not restrict Cu and Zn uptake, as M3 and M5 media had higher amounts of these micronutrients (Table 4). These results corroborate those reported by Trettel et al (2018b), where Ocimum basilicum plantlets maintained in MS medium with 60 g L -1 of sucrose and 4.5 g L -1 of actived charcoal did not show an increased plantlets growth, and these micronutrients did not contribute to adsorption of Cu and Zn.…”
Section: Different Compositions Of Ms Mediumsupporting
confidence: 92%
“…The higher amounts of macronutrients, especially the nitrogen associated with the plant growth regulators (Table 3), promoted an increase in the number of leaves in the T4 medium (Table 2). Studies have reported that O. basilicum plants are responsive to high amounts of nitrogen and plant growth regulators to promote leaf emission (SILVA et al, 2017;TRETTEL et al, 2018a). Nitrogen is a constituent of the chlorophyll molecule (GREENWAY et al, 2012) and plant growth regulators, mainly cytokinins, contribute to the expression of genes that act on the cell cycle and promote leaf emission (TANK; THAKER, 2011; NEELAKANDAN; WANG, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the root growth of O. basilicum seedlings and other species of the Lamiaceae family, it has been verified that a reduction in nutrient concentration in the culture medium favored the growth and mass production of the root system. For example, the 'Genovese' and 'Basilicão Roxo' basil cultivars exposed to a 70-80% saline concentration showed an increase in root length and mass (SILVA et al, 2017;TRETTEL et al, 2018a). For other species of the Lamiaceae family, a reduction of up to 50% in salts favored root system growth (FADEL et al, 2010;SWAMY;MOHANTY;ANURADHA, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations